Tracing Spiritual Well-Being Through the Journey of Life Without Both Parents: A Study in Orphaned Adolescents - Kabelen, Yosepha Putri; Huwae, Arthur (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
Adolescence is a crucial period because it is a transition to adulthood. Adolescents in general are different from orphaned adolescents because they receive guidance from their parents. Meanwhile, orphaned adolescents experience many heavier things because they grow up without parents, which makes them lose their direction in life and have difficulty achieving spiritual well-being. If traced further, the achievement of spiritual well-being is the desire of everyone, including orphaned adolescents. However, the dynamics that they go through are not easy and are full of various obstacles and risks. For this reason, the purpose of this study is to determine the portrait of the spiritual well-being of orphaned adolescents. The method used in the research is qualitative with an interpretative phenomenology design. The participants were 3 orphaned teenagers using a purposive sampling technique with the criteria of 18 years old to 22 years old and having been orphaned since childhood. The findings of this study are the existence of self-awareness in orphaned adolescents that allows them to connect with themselves, the emergence of forgiveness, the ability to regulate emotions, and self-acceptance. This research can be an illustration for orphaned adolescents so that in the future they can continue to develop spiritual well-being in their daily lives to have a more prosperous life. Apart from that, support from the surrounding environment is also expected to be one of the important parts that can facilitate orphaned adolescents to be able to help them assess themselves to be meaningful and can continue to live a better life than before. Masa remaja merupakan masa yang krusial karena merupakan peralihan menuju dewasa. Remaja pada umumnya berbeda dengan remaja yatim piatu karena mendapat bimbingan dari orang tua. Sedangkan, remaja yatim piatu mengalami banyak hal yang lebih berat karena tumbuh tanpa orang tua yang membuat mereka kehilangan arah hidup, dan kesulitan mencapai kesejahteraan secara spiritual. Padahal jika ditelusuri lebih jauh bahwa pencapaian spiritual well-being menjadi keinginan dari semua orang, termasuk juga remaja yatim piatu. Akan tetapi, dinamika yang dilalui oleh mereka tidaklah mudah dan penuh dengan berbagai rintangan dan risiko. Untuk itu, tujuan penelitian ini untuk mengetahui potret spiritual well-being remaja yatim piatu. Metode yang digunakan dalam penelitian adalah kualitatif dengan desain fenomenologi interpretatif. Partisipan merupakan 3 orang remaja yatim piatu dengan menggunakan teknik purposive sampling dengan kriteria berusia 18 tahun hingga 22 tahun dan telah menjadi yatim piatu sejak kecil. Temuan penelitian ini adalah adanya self-awareness pada remaja yatim piatu yang membuat mereka bisa terhubung dengan dirinya sendiri, munculnya sikap forgiveness, memiliki kemampuan meregulasi emosi dan sikap penerimaan diri. Penelitian ini dapat menjadi gambaran bagi remaja yatim piatu agar kedepannya mereka bisa terus mengembangkan spiritual well-being dalam kesehariannya guna memiliki kehidupan yang lebih sejahtera. Terlepas dari itu, dukungan dari lingkungan sekitar juga diharapkan menjadi salah satu bagian penting yang dapat memfasilitasi remaja yatim piatu untuk bisa membantu mereka menilai diri menjadi berarti, dan bisa terus menjalani kehidupan lebih baik dari sebelumnya.